ASSESSMENT OF TWO-WHEELED VEHICLE EMISSIONS IN THE VICINITY OF THE ENVIRONMENTAL ENGINEERING DEPARTMENT, UNIVERSITAS TADULAKO, INDONESIA - Maulida, Fatimah; Mawaddah, Nurul; Zurfi, Alfian; Prayogo, Wisnu; Nur, Aulia Mustaqiman (Directorate of Research and Community Service (DRPM), 2025)
Two-wheeled motor vehicles are a major source of urban air pollution. This study investigates the emissions of carbon monoxide (CO) and hydrocarbons (HC) from motorcycles operating within the Environmental Engineering Department of Universitas Tadulako. Emission data were collected using direct measurements with an automotive emission analyzer across various motorcycles differing in age, fuel type, and engine condition. The findings reveal that, although the average emission levels generally meet the national standards (Ministerial Regulation No. 8/2023), motorcycles using lower-grade fuel (Pertalite) emit higher concentrations of CO and HC compared to those using higher-grade fuel (Pertamax). Furthermore, both CO and HC emissions increase with the age and mileage of the vehicle. The correlation analysis indicates that older vehicles and those with higher mileage tend to release more pollutants due to reduced engine efficiency. These results underscore the importance of regular vehicle maintenance, the use of higher-quality fuels, and awareness campaigns to reduce air pollution on campus. The study supports the development of environmentally friendly transportation policies within educational institutions. ASSESSMENT OF TWO-WHEELED VEHICLE EMISSIONS IN THE VICINITY OF THE ENVIRONMENTAL ENGINEERING DEPARTMENT, UNIVERSITAS TADULAKO, INDONESIA